Peningkatan Hasil Belajar Pak Bp Dengan Penerapan Model Pembelajaran Problem Based Learning Melalui Diskusi Kelompok Pada Peserta Didik Fase D Kelas IX Uptd SMP Negeri 3 Lolofitu MOI - Bezisokhi Zai; Mawarni Gea; Agusinus Mulyono (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This research explores the effectiveness of the Project Based Learning (PBL) method in enhancing student learning outcomes in Catholic Religious Education and Character Education in Phase D for ninth-grade students at UPTD Negeri 3 Lolofitu Moi. Using a quantitative approach, this study involved 10 students from the school and employed an experimental design to analyze the impact of PBL on understanding the material related to Rights and Obligations as Members of the Church and Society. Data were collected through observations of teacher activities, student activities based on observation sheets, group discussions, the learning process, and the completion of student worksheets. The results showed that teacher activity in implementing PBL improved from 68.7% (good) to 98.8% (excellent). The findings indicate a significant increase in quiz test scores, from 50% (good) student mastery to 90% (excellent), suggesting progress in material comprehension. Further observations revealed that student engagement in the learning process and group discussions increased from 68.7% (good) to 98.4% (excellent), which not only enriched their learning experience but also developed collaborative skills and critical thinking. These findings confirm that the PBL method, with a focus on collaborative learning, can be an effective strategy for enhancing learning outcomes and student motivation in religious education. This study recommends the broader implementation of the PBL method in religious education curricula, as well as further research to explore other variables that may influence student learning outcomes.